Money and inflation in Malaysia: an analysis of causality (1970-92) - Abdullah, Ahmad Zainuddin; Yusof, Zulkornain (Universiti Putra Malaysia, 1994)
This paper investigates the causal relationship between money supply and rate of inflation using Malaysian data for the period 1970-92. The Granger methodology was adopted and results generally indicate a bidirectional relationship between money supply and the rate of inflation. In specific, money supply causes inflation for all cases (MI, M2 and the various choices of lag-lengths of the independent variable) while inflation causes money supply for all cases except for M₂ at lag 12 and M1 at lag 8 for the equal lag-length analysis.